Evaluation of Estridiol and Some Antioxidant in Breast Cancer Iraqi Women - Nsaif, Ghufran Saad; Abdallah, Amer Hassan; Ahmed, Najwa Shehab; Alfatlawi, Wafaa Raji (Al-Nahrain Journal of Science, 2018)
Cancer is the second reason of deaths worldwide while breast cancer is the more spread cancer in women, comprising 29 % from all cancers that they are affected Samples were obtained from patients undergoing surgery in center from breast cancer in oncology teaching hospital Al-Eluia hospital for woman care All blood samples were taken of the patients (110 women) and divided into four groups benign, malignant, radiotherapy and control group In order to measurement estrogen levels which are influenced by the menstrual cycle, the main groups were furthermore divided into sub-groups, premenopausal and postmenopausal women The mean value ± SE of Body Mass Index (BMI) for control, benign, malignant and radiotherapy breast cancer were showed a non-significant change in the comparison of groups according to the Duncan test Estrogen were increased before therapy but decreased following therapy The levels of malondialdehyde (MDA)were elevated in patients after radiotherapy The mean value ± SE of vitamin E were decreased in studied groups Present study aims to study the effects of serum estrogen, vitamin E and antioxidant status in breast cancer patients